Construction and validation of the questionnaire Satisfaction of users in Dentistry services. Cienfuegos, 2018 - José Luis Capote Femenías; Amalia Peña Rosell; Teresita Barrios Pedraza; Gretchen LLanes Bugallo; Neylin Lopez Ramil (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Currently, users of dental services have different expectations about dental services and are more demanding in relation to the quality of the service. To measure the level of satisfaction of users is a complex task which requires valid and reliable instruments. Objective: to validate an instrument that allows the assessment of the level of users´ satisfaction of the Comprehensive General Dentistry service. Methods: Study of technological Innovation, in the sub-system of dental service in the Comprehensive General Dentistry Specialty. The construction of this questionnaire was done by means of expert criteria and the methodology proposed by Moriyama. Its reliability was determined by the use of text-retext method, and Spearmen coefficient was calculated. Internal consistency was analyzed by alpha coefficient of Cronbach. The content was validated by consulting a second group of experts. For the validation of this construction the method of extreme groups was used and the test of measurement comparison of independent samples was used with an confidence interval of 0,05. Results: the questionnaire was defined as unidimensional with four categories and 10 selected items. The results of the reliability test and validity were satisfactory. Conclusion: the satisfaction questionnaire in Dentistry services is an adequate instrument and with appropriate criteria for its use in the research field, so as in the practice of these services, since it allows to obtain data about users' satisfaction.